Sustaining and Strengthening Conservation Capacity by Anticipating and Preparing for Change in the Greater Virunga Landscape - D, John; MacArthur, Catherine T (My University, 2012)
Executive summary The project “Sustaining and Strengthening Conservation Capacity by Anticipating and Preparing for Change in the Greater Virunga Landscape” has been successful in advancing the knowledge, capacity and preparedness required for long-term conservation in the Greater Virunga Landscape. The rich and unique natural heritage of the Albertine Rift has made it a focus for the MacArthur Foundation. The Greater Virunga Landscape represents the most significant concentration of globally significant biodiversity within this region. This landscape provides a microcosm of the many challenges facing conservation across the globe. Increasing human populations, escalating demand for agricultural land, mounting pressure on water and natural resources, the spectre of climate change, alien invasive species and a number of other threats all pose potential dangers to conservation outcomes. Successful long-term conservation outcomes in the Greater Virunga Landscape are far from guaranteed. It will require well informed judgement from those in positions of influence to negotiate these challenges and maintain the region’s conservation values. The purpose of this project was to bolster local conservation knowledge, capacity and preparedness. This 3-year project was led by the Institute of Tropical Forest Conservation (ITFC) and began in January 2009. We organised our activities around four linked goals. We used these as headings to structure our report. 1. Build effective partnerships and alliances to enhance flexible science-based conservation and management in the Albertine Rift. 2. Maintain, evaluate and improve long term monitoring and evaluation to enhance flexible conservation and management in the Albertine Rift. 3. Increase preparedness to recognize, mitigate and adapt to climate change and other emerging challenges in the Albertine Rift. 4. Strengthen capacity and communication for science-based conservation in a changing world. Effective partnerships and alliances While maintaining a strong relationship with the Uganda Wildlife Authority (UWA) and other local stakeholders through many joint activities and meetings (Appendix A), the grant has allowed the institute to maintain and expand its research and partnerships in Uganda, Rwanda and beyond (see Appendix B). The three information sharing workshops during this grant period have been well attended by key regional stakeholders in conservation, development and capacity building (Appendix D). Discussions about priorities for conservation management, in particular of the Bwindi and Mgahinga Conservation Area (BMCA), have guided our research planning and proposal writing for additional funding. Many new research partnerships have been attempted, and several were or are still being developed. ITFC jointly developed successful grant proposals with the Tropical Ecosystem Assessment and Monitoring (TEAM, of Conservation International), the Wildlife Conservation Society (WCS), Fauna and Flora International (FFI), the International Institute for Environment and Development (IIED) and the Bwindi and Mgahinga Conservation Trust (BMCT). We have increased ITFC’s visibility, locally, nationally, regionally and internationally. Lessons from the project have been shared via meetings, presentations, publications, our website, our blog, through training seminars and via local and international research and conservation networks. The grant allowed us to employ a communications officer, who overhauled our website www.itfc.org. ITFC also Final report ITFC to MacArthur Foundation for grant 19722 Page 5 ITFC in starting monthly systematic phenology monitoring, as well as establishing permanent vegetation monitoring plots at two high altitude (>4000m.a.s.l.) locations, the first ones in Africa. In the course of this grant, ITFC organised 3 Information Sharing workshops, well attended by partner organisations in the Albertine Rift. At the occasion of the final workshop of this grant, we discussed monitoring priorities for the years ahead with conservation managers and partner organisations. Issues topping the agenda appear to be Mountain gorilla behaviour (increasingly foraging outside the park, in community land), the prevention and management of human-wildlife conflict, the pressure for and management of resource use by communities and the assessment and monitoring of the impact of conservation and development interventions on changes in community wellbeing and attitudes. Minutes of these group discussions are added as Appendix H. Climate change and other emerging challenges During this grant’s period, a total of 12 Masters’ and 3 PhD students were supported by ITFC. Thanks to the scholarship program made possible by this MacArthur grant, 9 Ugandan Masters’ students Final report ITFC to MacArthur Foundation for grant 19722 Page 6 wrote weekly blogs on www.wildlifedirect.org for a wider conservation interested audience. Web-paged requests have risen from the low-hundreds to over one-thousand per day. ITFC continues to work for impacts in terms of conservation and development benefits (Appendix F) and to share its work with a global community through its website www.itfc.org. ITFC has been well covered in the local and global media with stories on BBC radio and television, in various papers, including The Observer and National Geographic and in Uganda’s Monitor. A questionnaire survey we carried out among participants of the closing workshop of this grant, showed that two thirds of our partner’s rate ITFC’s performance and collaboration as ‘good’ and the remainder as ‘satisfactory’. Appendix I includes more detailed comments and suggestions. Long term monitoring and evaluation ITFC’s long term monitoring activities were reviewed, with various recommendations for improved effectiveness (Appendix E). These are being taken up by UWA in the development of a new General Management Plan for the Bwindi and Mgahinga Conservation Area, expected to be finalised later in 2012. ITFC kept monitoring the impacts of resource offtake on the forest, and continued and improved the weather data collection by UWA. We now have 12 and 25 years respectively of continuous data on these important aspects of BMCA, which were defined as crucial by stakeholders at the start in the late 1990-ies. The review led us to discontinue the water quality monitoring as well as the vegetation monitoring of the Kyabiranyuma swamp, till further notice. Fire monitoring is taken over by UWA. New activities include the TEAM project (in collaboration with UWA) and an increased emphasis on phenology. We have revised guidelines and protocols for the climate data collections to better reflect the constant changes in UWA staff that have plagued these activities. The sustainability of monitoring programs has always been a worry to ITFC: few donors have an interest supporting such activities, as results may not be forthcoming within the time span of most grants. We therefore invested effort in convincing Conservation International, through the Wildlife Conservation Society, to add Bwindi-ITFC to its global network of field sites for monitoring climate change. ITFC and UWA partner in this program called Tropical Ecology Assessment and Monitoring (TEAM). We have just completed three full years of data collection, with vegetation monitoring in 6 permanent 1-hectare plots, automatic camera trapping of animals with 30 cameras, 30 days in 2 sites and an automatic climate station. Funding from the MacArthur Foundation to WCS for Climate Change studies supported received funding for their university fees, stipends and fieldwork expenses and contributed to this grant’s success by piloting studies into emerging conservation challenges in the Albertine Rift. Research questions were identified through consultation with local conservation managers and various academic experts and included assessments of carbon stocks inside and outside the protected forest, people’s migration, human-wildlife conflicts, altitudinal zonation ( a proxy for climate change), and invasive species. See a complete list in Appendix F. Four students have received their MSc award so far and 5 are still finalising their theses. Several students have submitted articles for peer reviewed science journals and several more plan to do so. We are proud that two of our first batch of Masters’ students are now enrolled in PhD programs, one with the University of Cambridge, UK, and one with the University of Eastern Finland. One more, a project staff member with ITFC since completing his MSc degree with MUST, is in an advanced stage of developing a proposal for a PhD. Additional funding from USAID, through a joint proposal with WCS-Uganda, allowed us to offer 3 more scholarships to Masters’ students. Two investigated the risk of rodents and baboons transferring diseases across the park-community boundary and one did an inventory of amphibians in Bwindi and checked the presence of the chytrid fungus, deadly to frogs and already causing decline in numbers of species across the globe. ITFC played an important role in various regional efforts to model the effects of climate change on conservation: we assisted the MacArthur funded project on the ‘Implications of Global Climate Change for Mountain Gorilla Conservation in the Albertine Rift’ (coordinated by the African Wildlife Foundation, International Gorilla Conservation Programme and EcoAdapt), set up high altitude vegetation plots in Rwenzori Mountains and Mount Elgon for the MacArthur funded Climate Change project (coordinated by WCS) and also through our participation in the TEAM global monitoring of climate change impacts. Capacity and communication for science-based conservation Several of our staff received field training and gained experience (systematic plot establishment and recording, phenology, data analysis etc) in the context of grant activities. Some went for formal training in statistics, camera trapping, science communication, research design, payments for environmental services and proposal writing. In particular, staff attended several courses in East Africa offered by the Tropical Biology Association (TBA). (see Appendix A). Two separate proposals for funding of education and dissemination activities were prepared by the Communications Officer of ITFC (in July 2011 we submitted “Education on Bwindi Impenetrable National Park as a World Heritage Site” to Pro Nature Fund, a Japanese conservation funding mechanism; in December 2011 we submitted a similar proposal “Increasing local pride in and support for conservation of Bwindi Impenetrable National Park” to Sea World & Bush Garden). Neither of these was granted. The Communication Officer assisted staff in improving presentations of their work, as well as internal and external communication skills. Additional issues As might be anticipated in a project of this scale and ambition we confronted and had to overcome a number of challenges and setbacks in accomplishing all the project objectives on time. The main challenges were caused by staff changes at ITFC and among our partner organisations. Notably the Uganda Wildlife Authority has appointed four different Conservation Area Managers and three different research and monitoring wardens over the last 3 years, substantially increasing the efforts needed to ensure effective engagement. Final report ITFC to MacArthur Foundation for grant 19722 Page 7 Maintaining monitoring programs remains a significant concern. Establishing long-term monitoring activities without clear sustained funding for such activities remains a concern. Similarly, short-term project funding cannot always attract the qualified staff that we might like as the positions lack security. The MacArthur Foundation permitted ITFC a no-cost extension of the grant for four months, to allow us to hold a larger scale closing workshop in March 2012 and round off our activities. We have written many new proposals in the last four years. Successful applications include two Darwin grants in conjunction with IIED another with FFI and a grant to WCS from DEFRA. Other successes have been the inclusion of Bwindi in the CI-WCS led TEAM project, a small grant from a private donor for developing outreach materials. ITFC feels it is particularly useful if we can find sustainable sources of support for post graduate students to do their field studies with us.
Keywords: Conservation; Landscape; Change